PENGEMBALIAN ASET DAN PENJATUHAN HUKUMAN MATI PADA TINDAK PIDANA KORUPSI - Kusyandi, Adi (Yustitia, 2022)
Although it has the potential to restore state losses, in its implementation there are still legal issues regarding the obstacles to the confiscation of assets in corruption cases. Assets are a series of processes or stages starting from collecting information or intelligence, evidence, tracing assets, freezing and confiscation of assets, trial processes, implementing court decisions or decisions, to handing over assets to the state. Returning assets is the responsibility of all law enforcement agencies authorized to investigate or prosecute criminal acts of corruption, in this case, the Indonesian National Police, the Indonesian Attorney General's Office, and the Corruption Eradication Commission. This effort, saidAgustinus, is constrained by the difficulty of proving the relationship between assets and criminal acts because confiscation and confiscation as regulated in the Criminal Procedure Code and the Criminal Code are still property-based. "In terms of legal substance, there are several weaknesses, for example, the rules for confiscation based on the Criminal Procedure Code are constructed to prove criminal acts, not to return assets,"